2007
DOI: 10.1371/journal.pone.0000692
|View full text |Cite
|
Sign up to set email alerts
|

Altered T-Cell Function in Schizophrenia: A Cellular Model to Investigate Molecular Disease Mechanisms

Abstract: Despite decades of research into the aetiology and pathophysiology of schizophrenia, our understanding of this devastating disorder remains incomplete, with adverse consequences for both diagnosis and treatment. Here we investigate whether differences between patients and controls can be observed in peripheral patient tissue, with a view of establishing a means for dynamic investigations into cell function. In vitro stimulation of peripheral blood CD3+ pan T cells with anti-CD3 (clone OKT3) was used to investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(64 citation statements)
references
References 35 publications
2
59
1
1
Order By: Relevance
“…There is increasing evidence, both from the literature and from studies carried out within our own group, to suggest that disease-related changes can be detected outside the brain (11,13,14). Various immune alterations have been reported previously in schizophrenia (15)(16)(17)(18), and disease-related changes are detectable in T cells (19). In the present study we extended our search for biomarkers to proteomics profiling of peripheral blood CD3 ϩ T cells.…”
Section: Molecular and Cellular Proteomics 7: 1204 -1213 2008mentioning
confidence: 76%
“…There is increasing evidence, both from the literature and from studies carried out within our own group, to suggest that disease-related changes can be detected outside the brain (11,13,14). Various immune alterations have been reported previously in schizophrenia (15)(16)(17)(18), and disease-related changes are detectable in T cells (19). In the present study we extended our search for biomarkers to proteomics profiling of peripheral blood CD3 ϩ T cells.…”
Section: Molecular and Cellular Proteomics 7: 1204 -1213 2008mentioning
confidence: 76%
“…The immune responses to changes of cellular environ ment have been measured and reported to be altered in people with Sz [62,65,66] . For example, out of 107 immune molecules, less IL-18 and more S100A12 (ENRAGE) were secreted by blood cells in ex vivo cultures obtained from firstonset people with Sz compared to controls following stimulation condition with a T cell stimulator (i.e., anti-CD28/CD49d) [66] , an effect replicated in an independent cohort [66] .…”
Section: Bdnfmentioning
confidence: 99%
“…Long-term activation could then lead to desensitization of the proliferation responses as indicated by a reduced proliferative rate of schizophrenia patient-derived T cells, implying that patient T cells have become refractory to stimulation and respond significantly less to in vitro stimulation. 17,18,41 T-cell activation in the patient's body, as shown here through elevated levels of CD25 high and CD69 high , could furthermore help to recruit T cells to cross the blood-brain barrier to foster communication between the central nervous system and the immune system. Previous studies have shown that T cells have beneficial effects on a damaged central nervous system.…”
Section: Discussionmentioning
confidence: 81%
“…[13][14][15][16] T lymphocytes have integral function in cell-mediated immunity and are involved in host defence against infectious agents. Peripheral changes in the immune system of schizophrenia patients, such as decreased cellular immune response 17,18 and altered cytokineexpression, 19 have been reported. However, these immunological findings are inconsistent and controversial due to different methodological approaches, the heterogeneity of sample sourcing and acquisition, as well as lack of controls for confounding factors such as smoking.…”
Section: Introductionmentioning
confidence: 99%